WOMEN'S IDENTITY, POWER, AND AGENCY IN THE POETRY OF ASHHADU AN LA IMRO'AN ILLA ANTI BY NIZAR QABBANI: A SEMIOTIC STUDY OF RIFATERRE - Mellinda Raswari Jambak; Kurnia Amalia Ilmi; Halimi Halimi (Journal of Arabic Literature (JaLi), 2024)
The society's view of women so far depicts that they do not have identity, power, or the ability to make changes to themselves or others. In contrast to the content of Nizar Qabbani's poem, the poet describes how women can contribute to the lives of others. This research aims to reveal the forms of identity, power, and agency of women in the poem Asyhadu An La Imro'an Illa Anti by Nizar Qabbani. Rifaterre's semiotic theory is used to analyze poetry. This type of research is qualitative. The primary data source of this research comes from the poem Ashhadu An La Imro'an Illa Anti by Nizar Qabbani. Meanwhile, secondary data sources come from journals, artifacts, proceedings, and relevant books. The data collection technique used is the reading and recording technique. The data analysis techniques are data reduction, data exposure, and conclusion drawn. The results of this study show that there are 6 identities of women, namely diligent in all things, motherhood, generosity, attractiveness, companionship and protector, and bravery. The two forms of women's power are to make men helpless and to have power over the laws of the world. As well as a form of women's agency, which is to change life to be more colorful.